QAS 2022
DOI: 10.47750/qas/23.189.40
|View full text |Cite
|
Sign up to set email alerts
|

Can Performance Be Achieved Through the Role of Normative Commitment as Mediation and Innovation as Moderator: Driven by Good Governance, Driving Human Resources Intrinsic and Motivation?

Abstract: The purpose of this study was to analyze and prove the effect of Good Governance and Competency of Human Resources and Intrinsic Motivation on Normative Commitment and Employee Performance with Innovation asModerating Variable at the Regional Revenue Agency of East Kalimantan. This study uses a survey technique by distributing questionnaires; The data obtained were processed using the WarpPLS software statistical method. The population of this study were all employees of the Regional Revenue Agency in East Kal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 20 publications
(29 reference statements)
0
1
0
Order By: Relevance
“…Good et al [68] and Suharto et al [69] found that intrinsic work motivation significantly affects employee performance. Intrinsic work motivation gives employees a great deal of autonomy and the opportunity to choose and carry out their work in an innovative way [70].…”
Section: Intrinsic Work Motivation and Employee Performancementioning
confidence: 99%
“…Good et al [68] and Suharto et al [69] found that intrinsic work motivation significantly affects employee performance. Intrinsic work motivation gives employees a great deal of autonomy and the opportunity to choose and carry out their work in an innovative way [70].…”
Section: Intrinsic Work Motivation and Employee Performancementioning
confidence: 99%